Functional strength training and movement performance therapy produce analogous improvement in sit-to-stand early after stroke: early-phase randomised controlled trial. Issue 3 (September 2017) - Kerr, A.; Clark, A.; Cooke, E.V.; Rowe, P.; Pomeroy, V.M.
Abstract: Objectives: Restoring independence in the sit-to-stand (STS) task is an important objective for stroke rehabilitation. It is not known if a particular intervention, strength training or therapy focused on movement performance is more likely to improve STS recovery. This study aimed to compare STS outcomes from functional strength training, movement performance therapy and conventional therapy. Design: Randomised controlled trial. Setting: Acute stroke units. Participants: Medically well patients ( n = 93) with recent (<42 days) stroke. The mean age of patients was 68.8 years, mean time post ictus was 33.5 days, 54 (58%) were male, 20 showed neglect (22%) and 37 (40%) had a left-sided brain lesion. Interventions: Six weeks of either conventional therapy, functional strength training or movement performance therapy. Subjects were allocated to groups on a random basis. Main outcome measures: STS ability, timing, symmetry, co-ordination, smoothness and knee velocity were measured at baseline, outcome (after 6 weeks of intervention) and follow-up (3 months after outcome). Results: No significant differences were found between the groups. All three groups improved their STS ability, with 88% able to STS at follow-up compared with 56% at baseline. Few differences were noted in quality of movement, with only symmetry when rising showing significantly greater improvement in the movement performance therapy group; this benefit was not evident at follow-up. Conclusions: Recovery of the STS movement is consistently good during stroke rehabilitation, irrespective of the type of therapy experienced. Changes in quality of movement did not differ according to group allocation, indicating that the type of therapy is less important. Clinical trial registration numberNCT00322192 .